Equidade no acesso ao transplante renal em Belo Horizonte, 2000-2005 - Elaine Leandro Machado (2007)
Background: The world growth in the number of patients with Chronic Renal Failure has reached epidemic rates. Only by using renal replacement therapies (dialysis) or renal transplantation, the patients survival is possible. The renal transplantation is the choice treatment: it offers better survival and quality of life and it is also more cost effective than dialysis. Brazil has the greatest public health transplantation system in the world and, although the increasing of this activity, it is not sufficient because of the lacking offer of organs and an increasing demand that lead to an increasing of the awaiting list. The knowledge of the realsituation of transplantations in Brazil is precarious because of the lack of trustworthy epidemiological data. Objectives: Describe and analyze the access to renal transplantation of patients subscribed in the awaiting list in Belo Horizonte/MG, between. Methods: This is an observational, longitudinal study, using primary and secondary data. Socio- demographic and clinical variables of patients residents in BH, over 18 years old, subscribed in the kidney waiting list between 01/01/2000 and 12/31/2004, were collected from Renal Receptors Database and from reports on clinical resolution of patients sent to Minas Geraiss Transplantation Center. Professionals involved in regulation of transplantation were interviewed. Descriptive and comparative statistical analysis and interview thematic were made. Results: Patients that reached renal transplantation were younger and professionally active than those who didnt. They presented, more frequently, blood type A, glomerulonephritis as main cause of ESRD, less prevalence of diabetes, less time of waiting from the beginning of dialysis to the subscription inthe waiting list than the non-transplanted patients. It was detected that the number of living donors remains greater than the cadaveric donors in the period of time studied. Conclusion: The results suggest that socio-demographic and clinical factors influence the access to renaltransplantation for ESRD patients in Belo Horizonte. It was also verified that the access for ESRD patients to transplantation is not restricted only from the subscribing in the waiting list to gain a kidney being present since the primary care